(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Varmam- a discrete medical science and a great contribution of Siddhars to Tamil Nadu. It encompases Varma martial arts, Varma therapy, internal and external medicines. Varma therapy and medicines effectively treat neuro musculoskeletal conditions which is admirable. Shoulder pain is most common orthopaedic condition. It is the third common cause of musculoskeletal consultations in primary care. Approximately 1% of adult develops new shoulder pain annually. Common pathological conditions of shoulder like rotator cuff disorders and adhesive capsulitis etc exhibits similar clinical features like pain and stiffness of shoulder joint and restricted movements. Varma therapy rearranges and regulates the “Vaasi” and consequently helps to maintain the equilibrium of trihumours (Vatham, Pitham, Kapham). This review article explicates the Varma points for the treatment of shoulder pathological conditions, the exact anatomical location of Varma points and the appropriate method of its manipulation, certainly a key to further research articles.